WORK ETHICS AND EFFICIENCY OF SOCIAL WELFARE AND DEVELOPMENT OFFICE PERSONNEL IN CAPIZ - Borres, Janice B (President University, 2024)
Work ethics and efficiency are the essential components that help personnelunderstand the importance of ethical standards in achieving the goals and quality of servicesrendered in an organization. This study explored the degree of work ethics and the level ofefficiency of the 160 Municipal Social Welfare and Development Office (MSWDO) personnelin Capiz, as well as their correlation. The purpose of this study is to provide data on theP/C/MSWDO on how personnel perceived their work ethics and efficiency in dealing withtheir tasks and the delivery of their service to the clientele in their respective organizationwhether they possess the characteristics, skills, and competence that is needed in today’sworkplace, practically and timely. The sample size was taken from the total population with amargin of error set at 0.03 using the Slovin’s formula. This study utilized the quantitativeresearch design, employing the correlational method. A researcher-made questionnaire,frequency count, percentage, mean, t-test, and Pearson r correlation were used to collect andanalyze data. The findings showed that the degree of work ethics and level of efficiency werevery high. The respondents' age significantly affects their work ethics and efficiency. Likewise,the length of service also affects their efficiency towards work. Finally, the degree of workethic and level of efficiency were interrelated. It is imperative, therefore, that a higher degreeof work ethics of MSWDO personnel can result in higher efficiency. Future researchers arerecommended to further the work ethics and efficiency constructs among governmentagencies.